Standing in the Threshold: Carpaccio’s Calling of Saint Matthew Reconsidered - Matino, Gabriele (Confraternitas, 2021)
In 1502 Vittore Carpaccio delivered the Calling of Saint Matthew to the Venetian Scuola Dalmata dei Santi Giorgio e Trifone, a confraternity founded in 1451 by the Dalmatian community residing in Venice. The painting’s recent restoration sponsored by Save Venice offers an opportunity to re-examine the work and reconsider its iconography. Building upon new visual and documentary evidence, this article argues that Carpaccio painted the tax collector Matthew not as a Jewish moneylender, as previously assumed, but as a Venetian moneychanger within his workplace, a banco de tapeto that once faced Campo San Giacomo at Rialto. An examination of Matthew’s gesture reveals that Carpaccio depicted the moment that preceded, rather than followed, the Evangelist’s decision to abandon his profession and follow Christ. This change to the traditional iconography, I suggest, should be regarded as a visual exemplum of Christian charity, the virtue central to the Scuola Dalmata’s devotional practices.